Penerapan Prinsip Kesetaraan Relasi Puskesmas Dengan Badan Penyelenggara Jaminan Sosial Berdasarkan Peraturan Badan Penyelenggara Jaminan Sosial Nomor 7 Tahun 2019 - Ardiansah; Eddy Asnawi; Dwi Agustina Fajarwati (Program Studi Akuntansi IKOPIN, 2022)
Health centers in the JKN/BPJS system have a major role in BPJS health participants. Quality services are services that must have basic requirements, namely, available and sustainable, easily accessible, easily accessible, acceptable and reasonable, and of good quality. The decline in the quality of FKTP can affect the calculation of capitation payments for FKTP. According to Article 4 of BPJS Regulation Number 7 of 2019 concerning Instructions for Implementation of Performance-Based Capitation Payments at first-level health facilities, the contact number is one indicator to see the utilization of the Puskesmas. If the quality of FKTP services decreases, it will certainly have an impact on the number of patient contacts with FKTP. Other impacts that arise are such as reduced capitation payments which have an effect on labor intensiveness in FKTP. This can cause a sense of injustice to the rights that should be obtained. This study aims to analyze the relationship between the Puskesmas and the Social Security Administering Body based on the Regulation of the Social Security Administering Body Article 4 Number 7 of 2019 and to find out the ideal concept of the relationship between the Puskesmas and the Social Security Administering Body based on Indonesian Positive Law. The research method used by the author is normative research which is carried out by finding the rule of law, legal principles, or legal doctrines, as well as searching literature using data bases to answer legal issues faced in writing. The application of the tariff applied by BPJS to Puskesmas is a capitation system, in which the payment of claims in advance every month at health facilities is based on the number of patients who register at the health facility without calculating the type and number of health services provided. This system is effective but pressures health facilities to serve with claims below the basic cost of health services so that health facilities are resistant and provide services that are meager and tend to be poor. Therefore, more effective policies are needed so that equality occurs in order to create good quality in health services. Policies related to the relationship between Puskesmas and BPJS must be based on the basis of the obligations of the State of Indonesia in guaranteeing the right of the people to obtain proper health services in accordance with Article 28 H and Article 34 of the 1945 Constitution of the Republic of Indonesia, as well as reviewing the responsibilities of the Government and the Government. Regions to provide health facilities that meet these standards and cooperate with BPJS Health in accordance with Articles 35 and 36 of Presidential Regulation Number 111 of 2013 concerning JKN.